Finding God without going out in search of Him. The beginning of the Book of Jeremiah (Jr 2: 1-19) - Sanz Giménez-Rico, Enrique (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The first words that Jeremiah addresses to Israel, as found in Jr 2, draw together important aspects of the book of the prophet from Anathoth: God’s Covenant with His people and the consequences of their disobedience and rejection of it. Within the quoted chapter, Jr 2, vv. 1-19 form a unit in which God condemns Israel’s infidelities and reminds her of His perennial fidelity which he has shown her in the past. Likewise, God reprimands His people for having walked the way of other gods and He reminds them of the golden age of the desert, the quintessential place of death, where He had led them while satisfying all their needs. Consideration of both actions; that of God and that of Israel, within this frame of reference allows one to draw a theological conclusion and its most logical outcome: Israel is able to encounter God without moving out in search of Him.
Keywords: desert; movement; rîb; covenant; infidelity